Sex steroid hormone levels associated with dopamine D2/3 receptor availability in people who smoke cigarettes - Zakiniaeiz, Yasmin; Gueorguieva, Ralitza; Peltier, MacKenzie R.; Verplaetse, Terril L.; Roberts, Walter; McKee, Sherry A.; Cosgrove, Kelly P. (Frontiers in Behavioral Neuroscience, 2023)
Introduction: Sex differences exist in tobacco smoking. Women have greater difficulty quitting smoking than men. Tobacco smoking is driven by the reinforcing effects of nicotine, the primary addictive component in cigarettes. Nicotine binds to nicotinic acetylcholine receptors facilitating dopamine release in striatal and cortical brain regions. Dysregulated dopamine D2/3 receptor signaling in dorsolateral prefrontal cortex (dlPFC) is associated with cognitive deficits such as impairments in attention, learning, and inhibitory control that impede quit attempts. Sex steroid hormones such as estradiol and progesterone, influence drug-taking behaviors, through dopaminergic actions, suggesting that their influence may explain sex differences in tobacco smoking. The goal of this study was to relate dlPFC dopamine metrics to sex steroid hormone levels in people who smoke and healthy controls. Methods: Twenty-four (12 women) people who smoke cigarettes and 25 sex- and age-matched controls participated in two same-day [11C]FLB457 positron emission tomography scans, one before and one after amphetamine administration. D2R availability (BPND) at baseline and after amphetamine administration were calculated. On the same day, plasma samples were collected for analysis of sex steroid hormone levels: estradiol, progesterone, and free testosterone. Results: Women who smoke had trending lower levels of estradiol than sex-matched counterparts. Men who smoke had higher levels of estradiol and trending higher levels of free testosterone than sex-matched counterparts. In women only, lower estradiol was significantly associated with lower pre-amphetamine dlPFC BPND. Discussion/Conclusions: This study demonstrated that lower estradiol is associated with lower dlPFC D2R availability in women which may underlie difficulty resisting smoking.